2006
DOI: 10.1152/ajpendo.00201.2006
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily administration of CJC-1295, a long-acting growth hormone-releasing hormone (GHRH) analog, normalizes growth in the GHRH knockout mouse

Abstract: Although the majority of children with isolated growth hormone (GH) deficiency have a good growth response to GH-releasing hormone (GHRH), the use of this therapeutic agent is limited by its very short half-life. Indeed, we have shown that, in mice with GHRH gene ablation (GHRH knockout; GHRHKO), even twice-daily injections of a GHRH analog are unable to normalize growth. CJC-1295 is a synthetic GHRH analog that selectively and covalently binds to endogenous albumin after injection, thereby extending its half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Because M 3 mAChRs are expressed in the hypothalamus at relatively high density (17,18), we speculated that hypothalamic M 3 receptor activity might be required for the proper function of GHRH neurons, resulting in the observed hypoplasia of the anterior pituitary and reduced longitudinal growth of Br-M3-KO mice. Consistent with this notion, we found that treatment of Br-M3-KO mice with CJC-1295, a synthetic GHRH analog (19)(20)(21), restored normal pituitary size and serum GH and IGF-1 levels, and normal longitudinal growth. The ability of CJC-1295 to rescue the various hormonal and morphological deficits of Br-M3-KO mice supports the concept that the primary defect underlying the dwarf phenotype of these mutant mice does not reside in the pituitary gland itself but most likely involves impaired function of hypothalamic GHRH neurons.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Because M 3 mAChRs are expressed in the hypothalamus at relatively high density (17,18), we speculated that hypothalamic M 3 receptor activity might be required for the proper function of GHRH neurons, resulting in the observed hypoplasia of the anterior pituitary and reduced longitudinal growth of Br-M3-KO mice. Consistent with this notion, we found that treatment of Br-M3-KO mice with CJC-1295, a synthetic GHRH analog (19)(20)(21), restored normal pituitary size and serum GH and IGF-1 levels, and normal longitudinal growth. The ability of CJC-1295 to rescue the various hormonal and morphological deficits of Br-M3-KO mice supports the concept that the primary defect underlying the dwarf phenotype of these mutant mice does not reside in the pituitary gland itself but most likely involves impaired function of hypothalamic GHRH neurons.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, we examined whether chronic administration of CJC-1295, a synthetic GHRH analog (19)(20)(21), was able to prevent the various hormonal and morphological deficits characteristic of Br-M3-KO mice. CJC-1295 selectively and covalently binds to endogenous albumin after injection, thereby extending its half-life and duration of action.…”
Section: Cjc-1295 Rescue Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, GHS could be more appropriate to restoring GH secretion in aged individuals than GHRH with its major limitation of a short half-life. Recent studies with CJC-1295, a long-lasting human GHRH analog, have shown that once-daily administration of the GHRH analog normalizes growth in the GHRH knockout mouse (1). In humans, prolonged stimulation of GH and IGF-I has been shown with a single subcutaneous administration of CJC-1295 in normal subjects (58).…”
Section: Discussionmentioning
confidence: 99%
“…GHRH-KO mice have also served to characterize a potent GHRH analog (i.e., CJC-1295) that exhibits a longer halflife and duration of action than the natural peptide because of its selective and covalent binding to endogenous albumin. 1 This analog has been successfully used in clinical trials, which highlights its potential utility as a therapeutic agent. 33 Indeed, since the discovery of the sequences crucial for GHRH somatotrophic activity, much effort has been invested in generating synthetic analogs with extended half-life and duration of action.…”
Section: Pathophysiological Implicationsmentioning
confidence: 99%